Nutrient intake and body composition of world karate champions: 4 case reports - Imamura, H.; Oda, K.; Tai, K.; Iide, K.; Yoshimura, Y. (Journal of Athletic Enhancement, 2018)
Background: The purpose of this study was to examine the nutrient intake and body composition of elite Japanese karate practitioners.